Sequence and expression analysis of the AMT gene family in poplar - Wu, Xiangyu; Yang, Han; Qu, Chunpu; Xu, Zhiru; Li, Wei; Hao, Bingqing; Yang, Chuanping; Sun, Guangyu; Liu, Guanjun (Frontiers in Plant Science, 2015)
Ammonium transporters (AMTs) are plasma membrane proteins that exclusively transport ammonium/ammonia. These proteins are encoded by an ancient gene family with many members. The molecular characteristics and evolutionary history of AMTs in woody plants are still poorly understood. We comprehensively evaluated the AMT gene family in the latest release of the Populus trichocarpa genome (version 3.0; Phytozome 9.0), and identified 16 AMT genes. These genes formed four clusters; AMT1 (7 genes), AMT2 (2 genes), AMT3 (2 genes), and AMT4 (5 genes). Evolutionary analyses suggested that the Populus AMT gene family has expanded via whole-genome duplication events. Among the 16 AMT genes, 15 genes are located on 11 chromosomes of Populus. Expression analyses showed that 14 AMT genes were vegetative organs expressed; AMT1;1/1;3/1;6/3;2 and AMT1;1/1;2/2;2/3;1 had high transcript accumulation level in the leaves and roots, respectively and strongly changes under the nitrogen-dependent experiments. The results imply the functional roles of AMT genes in ammonium absorption in poplar.